Principles of geotechnical engineering - Das, Braja M. (Brooks/Cole, 2001)
Intended as an introductory text in soil mechanics, the sixth edition of Das, Principles of Geotechnical Engineering, offers an overview of soil properties and mechanics, together with coverage of field practices and basic engineering procedure. With more figures and worked out problems than any other text on the market, this text also provides the background information needed to support study in later design-oriented courses or in professional practice.